1998
DOI: 10.1088/0741-3335/40/12/008
|View full text |Cite
|
Sign up to set email alerts
|

Trials of RF plasma production using different antenna geometries with magnetic field

Abstract: Plasma production studies excited by the radio frequency (RF) wave were carried out using various antenna configurations. Six types of side antennae, located outside the large cylindrical chamber, and two types of internal loop antennae were tested. The ion saturation current I is of a probe and the plasma emission were measured as a function of the filling pressure, the RF power and the magnetic field. With the increase in the power and the magnetic field, I is increased in most cases, while some of the anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The magnetic field present at the maximum of these density peaks has been shown experimentally 9 and numerically 12 to be approximately proportional to the wave frequency, and for frequencies of 13.56 MHz, occur at around 2-3 mT. 6,8,11 Associated with the density peaks of these low field helicons are corresponding peaks in the antenna loading resistance, 4,9,12 showing that the power transfer efficiency between the antenna and the plasma increases. Chen 4 has suggested that the formation of these peaks for m = 0 antennas is caused by constructive interference between forward waves launched by the antenna and reflected waves from an end plate.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The magnetic field present at the maximum of these density peaks has been shown experimentally 9 and numerically 12 to be approximately proportional to the wave frequency, and for frequencies of 13.56 MHz, occur at around 2-3 mT. 6,8,11 Associated with the density peaks of these low field helicons are corresponding peaks in the antenna loading resistance, 4,9,12 showing that the power transfer efficiency between the antenna and the plasma increases. Chen 4 has suggested that the formation of these peaks for m = 0 antennas is caused by constructive interference between forward waves launched by the antenna and reflected waves from an end plate.…”
Section: Introductionmentioning
confidence: 78%
“…2,4 At low magnetic fields ͑Ͻ10 mT͒, however, this proportionality no longer holds, and density peaks occurring over a narrow range of field values have been reported by several researchers. [5][6][7][8][9][10][11] These low field peaks have been studied over a fairly wide range of power and pressure values, with the large majority of work done making use of uniform magnetic field geometries. The magnetic field present at the maximum of these density peaks has been shown experimentally 9 and numerically 12 to be approximately proportional to the wave frequency, and for frequencies of 13.56 MHz, occur at around 2-3 mT.…”
Section: Introductionmentioning
confidence: 99%
“…A large helicon machine was built in Japan by Shinohara et al [74,75] It is shown in figure 27. Properties of the plasma have been studied with changes in the B-field uniformity and endplate conductivity [76], different types of antenna [77], including flat spirals tapped at various points and arrays of m = 0 loop antennas [78][79][80], and different sizes and aspect ratios of the discharge column, including diameters as small as 1 cm [81]. By biasing concentric-ring antennas, the radial electric field and plasma profile can be changed to study instabilities [82][83][84].…”
Section: Experiments By Shinohara Et Almentioning
confidence: 99%
“…Here, R c (0.4-0.5 ) and R p indicate the vacuum (i.e. circuit loss) and plasma loading resistances, respectively [39]. In this expression, the antenna loading (=P in divided by the square of the effective antenna current) is expressed as R p + R c (R c ) in the presence (absence) of the plasma, and the power coupling efficiency can be defined as R p /(R p + R c ).…”
Section: Dispersion Relationmentioning
confidence: 99%